2022
DOI: 10.1177/03635465221118377
|View full text |Cite|
|
Sign up to set email alerts
|

Isolated ACL Reconstruction Versus ACL Reconstruction Combined With Lateral Extra-articular Tenodesis: A Comparative Study of Clinical Outcomes in Adolescent Patients

Abstract: Background: Young patients undergoing anterior cruciate ligament (ACL) reconstruction (ACLR) are at a particularly high risk of graft ruptures compared with adults. Recent studies have demonstrated significant reductions in ACL graft rupture rates in high-risk adult populations when a lateral extra-articular procedure is performed, but comparative studies in pediatric and adolescent populations are currently lacking in the literature. Purpose/Hypothesis: The purpose of this study was to compare the clinical ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 51 publications
(82 reference statements)
1
32
1
Order By: Relevance
“…12,20,25,31 Nevertheless, the calculated NNT to prevent 1 rerupture was found to be 9 in our study, offering a promising improvement compared with the NNT of 14.3 reported by Getgood et al 12 Thus, we believe the LEAP procedure could potentially be a gamechanger in reducing rerupture rates among young athletes. Perelli et al 31 Monaco et al 25 Getgood et al 12 Laboudie et al 20 Current The RR for ACLR alone was calculated by taking the reciprocal of the reported RR for ACLR 1 LEAP (ie, 1/RR for ACLR 1 LEAP).…”
Section: Primary Outcome Measurescontrasting
confidence: 38%
See 2 more Smart Citations
“…12,20,25,31 Nevertheless, the calculated NNT to prevent 1 rerupture was found to be 9 in our study, offering a promising improvement compared with the NNT of 14.3 reported by Getgood et al 12 Thus, we believe the LEAP procedure could potentially be a gamechanger in reducing rerupture rates among young athletes. Perelli et al 31 Monaco et al 25 Getgood et al 12 Laboudie et al 20 Current The RR for ACLR alone was calculated by taking the reciprocal of the reported RR for ACLR 1 LEAP (ie, 1/RR for ACLR 1 LEAP).…”
Section: Primary Outcome Measurescontrasting
confidence: 38%
“…4,17,20,25,31,37 Regarding non-graft rupture related reoperations, our study reported a total rate of 10.6%, with no significant difference between the 2 groups. A similar rate of 10.8% was reported by Monaco et al 25 Although LEAP has not been shown to be associated with long-term osteoarthritis, 7,10,44 these findings are yet to be confirmed and validated in the pediatric population. Furthermore, the risk of these procedures in patients with open physes has not been well explored.…”
Section: Secondary Outcome Measuresmentioning
confidence: 50%
See 1 more Smart Citation
“…In recent years, there has been increasing interest in using extra-articular procedures to augment ACL reconstruction. Monaco et al reported lower rerupture rates with the addition of lateral extra-articular tenodesis (LET) when compared with isolated ACL reconstruction in the adolescent population 96 ; however, clinical outcomes were comparable. In a systematic review by Carrozzo et al ACL reconstruction augmented with LET in skeletally immature pediatric patients demonstrated a graft failure ranging from 0% to 13.6% at a mean follow-up of 50.1 months, with an overall graft failure rate of 4.65%.…”
Section: Outcomes After Surgical Treatmentmentioning
confidence: 99%
“…A sampling of other recent studies of ACL repair, reconstruction, or revision reconstruction in AJSM and OJSM reveals a variety of definitions of failure, including history of giving way, 16,19,21,22 laxity on instrumented physical examination, 2,6,15,16,19,22 MRI evidence of disruption, 2,3,6,10,15,21,22 graft rupture by history, 11 symptomatic instability, 10 and rerupture or symptomatic instability requiring revision surgery. 3,6,10,11,16,21 Studies often used multiple criteria, and symptoms suggestive of possible failure frequently led to further documentation by instrumented examination and MRI.…”
mentioning
confidence: 99%